Effects of task-oriented training on gait, balance and fear of falling after stroke: a case-study - Refacho, André (2022)
Introduction – Stroke is closely related to the increase of fall occurrence as well as the fear of falling, also a predisposing factor for falls. Changes in balance and gait, present even in more chronic phases, increase the risk of falls in this population. Objective – The aim of the study is to investigate the effects of task-oriented training on gait, balance, and fear of falling in a patient in the chronic phase after stroke. Methods – This study followed a case study methodology with a first assessment followed by seven weeks of task-oriented training and a second assessment at the end of the intervention. The tests used were the Falls-Efficacy Scale (FES-I), the Berg Balance Scale (BBS), the Barthel Index (BI), the Timed Up and Go Test (TUG), and the 4-meter Gait Speed Test (4MGS). Results – Clinical improvements in FES-I, BBS, BI, TUG, and 4MGS were observed.  Discussion/Conclusion – In 14 sessions of the task-oriented training program, improvements clinically significant in balance, gait, and fear of falling were observed in a patient in the chronic phase after stroke. Improvements in balance and gait functionality were accompanied by increased confidence in performing activities of daily living.